2014
DOI: 10.3389/fpsyg.2014.00483
|View full text |Cite
|
Sign up to set email alerts
|

Is a bird in the hand worth two in the future? Intertemporal choice, attachment and theory of mind in school-aged children

Abstract: Intertemporal choice is a decision-making dilemma related to outcomes of different entity located at different time points. Economic and psychological literature on this topic showed the phenomen of temporal discounting, i.e., the proclivity to devalue the outcome distant in time on the basis of the time delay necessary to obtain it. The goals of this research are to investigate two different components of intertemporal choice separately, namely time and outcome, in school-age children, and the possible link a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…Their results showed that in four-year-old children, accuracy in the false-belief ToM task was positively related to preferences for delayed rewards (stickers). In a similar recent study by Marchetti et al ( 2014 ), temporal discounting (with sweets) was found to be more predictive of performance on the ToM task than age, with children who were more patient scoring better on a first order false-belief task. These findings are in line with the SMIP's assumption that a greater SA capacity (which involves a greater capacity to inhibit egocentric bias) for others extends to future selves, promoting the subjective value of rewards for them.…”
Section: Introductionmentioning
confidence: 58%
“…Their results showed that in four-year-old children, accuracy in the false-belief ToM task was positively related to preferences for delayed rewards (stickers). In a similar recent study by Marchetti et al ( 2014 ), temporal discounting (with sweets) was found to be more predictive of performance on the ToM task than age, with children who were more patient scoring better on a first order false-belief task. These findings are in line with the SMIP's assumption that a greater SA capacity (which involves a greater capacity to inhibit egocentric bias) for others extends to future selves, promoting the subjective value of rewards for them.…”
Section: Introductionmentioning
confidence: 58%
“…All participants were tested with a paper-pencil ToM battery in order to assess their level of mentalizing development. For a more sensitive measurement of ToM ability, the battery consisted of a first order false belief task (Deceptive Box Task; Perner et al, 1987 ); two second order false belief tasks, Look-prediction task ( Astington et al, 2002 ; Antonietti and Giorgetti, 2006 ; Castelli et al, 2014 ) and Ice-cream story ( Perner and Wimmer, 1985 ; Marchetti et al, 2014 ) and advanced ToM tasks, i.e., a selection of four Strange Stories and their control task, the Physical Stories ( Happé, 1994 ; Happé et al, 1998 ; Mazzola, 2002 ). Each task provides for one or more control questions to test the understanding of the logical order and the explicit elements in the story without inferring mental states.…”
Section: Methodsmentioning
confidence: 99%
“…A previous meta-analysis on this relation (including 10 studies) showed a significant medium correlation, with the vast majority of studies reporting significant positive associations between attachment and EU (r = 0.34; Cooke et al, 2016). With regard to the association between attachment and FBU, the findings have been inconsistent, with studies reporting significant medium to large relations (e.g., Fonagy, Redfern, & Charman, 1997;Marchetti et al, 2014;McElwain & Volling, 2004;Meins, Fernyhough, Russell, & Clark-Carter, 1998;Meins et al, 2002;Meins, Bureau, & Fernyhough, 2018;Villachan-Lyra et al, 2015), and studies reporting null findings (e.g., Greig & Howe, 2001;Laranjo, Bernier, Meins, & Carlson, 2014;Meins et al, 2002, in preparation;Ontai & Thompson, 2008;Reese, 1998). These inconsistent findings have led researchers to speculate on whether attachment relates more strongly to thinking-about-feeling than to thinking-about-thinking (e.g., Greig & Howe, 2001).…”
Section: Empirical Studies On Attachment and Children's Fbu And Eumentioning
confidence: 98%
“…A few studies assessed FBU with multiple tasks (e.g., unexpected location and unexpected content task/appearance-reality task; e.g., Meins et al, 2002;Villachan-Lyra et al, 2015). Authors were also contacted to provide the correlations between attachment and individual false-belief tasks when only the association between attachment and a false-belief or EU sum score was reported, or the raw correlations were not reported in the paper (e.g., Marchetti et al, 2014;Meins et al, 2002;Ontai & Thompson, 2008;Oppenheim et al, 2005).…”
Section: Calculating Effect Sizesmentioning
confidence: 99%